PENGEMBANGAN DAN IMPLEMENTASI SISTEM INFORMASI ORGANISASI PADA PIMPINAN CABANG MUHAMMADIYAH KECAMATAN BATAM KOTA - Irmansyah Lubis, Ahmadi; Riyadi, Agung; Purnamasari, Dwi Amalia; Ardi, Noper; Mu'minin, Amirul; Suwarno, Suwarno; Ramadhan, Gilang Bagus (Journal of Community Service, 2024)
The management of an organization often has many obstacles such as less optimal management of organizational documents, news portals, financial reports, correspondence documentation, activity documentation or data collection of members of the organization. Therefore, a reliable management system is needed so that management in the organization can be carried out more optimally. Likewise with the management in the Muhammadiyah Branch Executive, Batam Kota District, a reliable system is also needed to support the movement of various activities in the organization. The website-based information system developed is an answer to this problem. This system can be used to manage various activities and monitor their progress as well as make it easier for administrators to collect data on their members. This system can also display various institutional news so that the public is more familiar with the Muhammadiyah Branch Executive of Batam Kota District as a community organization with Islamic nuances that also carries out da'wah activities to spread goodness. So this is an agenda in this community service activity for the development of information systems and assistance in the implementation of the system both for managers and users of the system, as well as as a concrete step for the contribution of Higher Education in empowering the community by applying scientific principles that are useful for the benefit of the community.